Avaliação do teste do coraçãozinho realizado em recém-nascidos do alojamento conjunto de um Hospital Terciário de janeiro de 2015 a julho de 2018 - Antonella Márcia Mercadante de Albuquerque do Nascimento; Vanuza Maria Rosa; Ana Barbara Queiroz Farias (Residência Pediátrica)
INTRODUCTION: Cardiovascular malformations are the most prevalent in newborns (NB). The prevalence of congenital heart disease (CHD) in Brazil has increased in recent years. The pulse oximetry test is currently used for the early diagnosis of CHD. OBJECTIVE: Analyze data on the pulse oximetry test carried out in the Rooming Room of a Tertiary Hospital as a screening for the diagnosis of critical congenital heart disease (CCHD), from January 2015 to July 2018. METHODOLOGY: Observational, quantitative and cross-sectional research through the analysis of data from the results of pulse oximetry test carried out at the service and research in electronic medical records of patients who had an altered test. RESULTS: 10,053 tests were carried out in the period with 42 changes. Of these, 15 (35.7%) had normal exams after repeating the heart test and/or performing the echocardiogram; 11 (26.2%) found heart disease on echocardiography; 13 (31%) did not repeat the heart test or did not perform an echocardiogram; 3 (7.1%) were not found. Echocardiograms were performed on 20 patients, with findings of heart disease found in 11 (false positive rate of 0.2% for pulse oximetry test). CCHD was observed in only 1 (Ebsteins Anomaly). The other findings were of acyanotic or pulmonary heart disease. CONCLUSION: It was evident that pulse oximetry test contributed to the diagnosis of CCC, to the realization of other diagnoses of CCC, as well as the need to correctly follow the protocol recommended by the SBP as a way to reduce hospitalization costs and echocardiograms.